lncRNA MAGI2-AS3 Prevents the Development of HCC via Recruiting KDM1A and Promoting H3K4me2 Demethylation of the RACGAP1 Promoter - Jian Pu; Jianchu Wang; Huamei Wei; Tao Lu; Xianjian Wu; Yi Wu; Zesheng Shao; Chunying Luo; Yan Lu (Elsevier, 2019)
Accumulating studies have implicated the role of long non-coding RNAs (lncRNAs) in the pathogenesis of hepatocellular carcinoma (HCC) through the regulating transcription and mRNA stability. A recent report has linked Rac GTPase-activating protein 1 (RACGAP1) to the early recurrence of HCC. The current study aimed to ascertain whether MAGI2 antisense RNA 3 (MAGI2-AS3) influences the development of HCC by regulating RACGAP1. MAGI2-AS3 expression was initially quantified in both the HCC tissues and cell lines. In order to elucidate the role of MAGI2-AS3 in the development of HCC, MAGI2-AS3 was overexpressed or silenced in HCC cells after which cell proliferation, apoptosis, invasion, and migration were evaluated. Chromatin immunoprecipitation (ChIP), RNA immunoprecipitation (RIP), and biotin-labeled RNA pull-down assays were conducted to determine the interactions among MAGI2-AS3, KDM1A, and RACGAP1. Finally, the effects of MAGI2-AS3 and RACGAP1 on the tumorigenesis of transplanted HCC cells in nude mice were evaluated. MAGI2-AS3 was found to be under-expressed in HCC tissues and cell lines. The restoration of MAGI2-AS3 was identified to markedly inhibit HCC cell growth, migrating ability, and invasiveness, and promote cell apoptosis. Interaction between MAGI2-AS3 and KDM1A was identified. KDM1A recruited by MAGI2-AS3 was found to promote H3K4me2 demethylation at the RACGAP1 promoter, which ultimately decreased the expression of RACGAP1. We also identified that RACGAP1 knockdown eliminated the stimulatory effects of MAGI2-AS3 silencing on the malignant phenotypes of HCC cells. Additionally, the expression of MAGI2-AS3 reduced tumor weight and size in HCC transplanted nude mice. Taken together, the key observations of the current study demonstrate the potential of MAGI2-AS3 as a tumor suppressor and a promising target for HCC treatment. Keywords: hepatocellular carcinoma, MAGI2-AS3, KDM1A, RACGAP1, demethylation, H3K4me2